2013
DOI: 10.2190/om.67.4.b
|View full text |Cite
|
Sign up to set email alerts
|

Participants' Recommendations for the Ideal Grief Group: A Qualitative Study

Abstract: Based on the results from the qualitative part of the study "Grief Groups in Norway" conducted in 2009-2011, this article focuses on grief group participants' recommendations for good or ideal grief groups. Participants have insightful observations about grief groups and how they can be improved, and taking their point of view seriously is one important way of ensuring that users of such group get an optimal experience from joining such groups. Using their experiences to adjust the structure and function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
1
13
0
3
Order By: Relevance
“…With time, some issues have changed and do not always seem appropriate to the experiences of recently bereaved participants, or in line with our graded-exposure approach. 23 This observation is consistent with the findings of Dyregrov et al 29 who found that bereavement group participants preferred to be with those whose experiences were similar. Another challenge relates to the program content.…”
Section: Discussionsupporting
confidence: 85%
“…With time, some issues have changed and do not always seem appropriate to the experiences of recently bereaved participants, or in line with our graded-exposure approach. 23 This observation is consistent with the findings of Dyregrov et al 29 who found that bereavement group participants preferred to be with those whose experiences were similar. Another challenge relates to the program content.…”
Section: Discussionsupporting
confidence: 85%
“…These are important points to consider when looking at the composition of group participants for this type of intervention. While there is debate about the advantages and disadvantages of homogenous over heterogeneous groups in bereavement care (Dyregrov, Dyregrov, & Johnsen, 2013;Neimeyer & Currier, 2009;Piper, Ogrodniczuk, Joyce, Weideman, & Rosie, 2007), it is important to ensure that participants do not feel isolated either by the nature of their loss or by personal characteristics such as age. One possible solution is to ensure that there are at least two people in the group with similar characteristics-be they nature of loss or age of participant.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the addition of more comprehensive qualitative data measurements such as in-depth interviews McFerran (2011) and focus groups Dyregrov et al (2013) could also be considered for future studies. These would also help in understanding the quantitative results and provide important corroborating evidence on the usefulness and impact of the different creative arts activities.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, we chose the novel format of a webinar to provide real-time simultaneous interaction between the therapists and the group participants. Grief group interventions can provide unique therapeutic elements such as universality of the suffering, group cohesiveness, role model learning, and interpersonal learning [30,31]. So far, studies of online group interventions have taken place mainly via videoconferencing.…”
Section: Internet-based Bereavement Interventionmentioning
confidence: 99%